2011
DOI: 10.4314/pamj.v8i1.71155
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pre-antiretroviral care and competition from traditional healers, crucial risk factors for very late initiation of antiretroviral therapy for HIV - A case-control study from eastern Uganda

Abstract: BackgroundAlthough WHO recommends starting antiretroviral treatment at a CD4 count of 350 cells/[µ]L, many Ugandan districts still struggle with large proportions of clients initiating ART very late at CD4 < 50 cells/[µ]L. This study seeks to establish crucial risk factors for very late ART initiation in eastern Uganda.MethodsAll adult HIV-infected clients on ART in Iganga who enrolled between 2005 and 2009 were eligible for this case-control study. Clients who started ART at CD4 cell count of < 50 cells/[µ]L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…As with any chronic disease, our results suggest that a relationship of trust between health care providers and patients is essential for the continuity of care and treatment . Consulting traditional healers has also been reported in several studies: it may represent a more accessible and cheaper alternative to academic medicine, but may also reflect a desire to distance oneself from modern medicine .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…As with any chronic disease, our results suggest that a relationship of trust between health care providers and patients is essential for the continuity of care and treatment . Consulting traditional healers has also been reported in several studies: it may represent a more accessible and cheaper alternative to academic medicine, but may also reflect a desire to distance oneself from modern medicine .…”
Section: Discussionsupporting
confidence: 68%
“…They emphasise the importance of patients' social contexts and their experience with care. The lower risk of TI>2d in PLWH living in a couple (compared with those having a main partner but living separately) suggests that such a relationship is probably associated with HIV disclosure and mutual support [17,[38][39][40][41][42]. Furthermore, PLWH, unsatisfied with the attention their doctor provided, were more likely to interrupt their treatment as were those who had consulted a traditional healer during the previous 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be explained by delayed HIV testing 12 or ART dropout resulting from conflict between traditional and clinic treatment advice 33 . However, the mixed state of quantitative evidence on the relationship between medical pluralism and ART uptake 15 , 16 mandates further research before firm inferences can be made.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study in a Ugandan ART clinic found that those who sought care from traditional/spiritual healers before coming to the clinic were more likely to have late ART initiation (CD4 < 50 cells/µL) than individuals who did not report seeking care from traditional/spiritual healers 15 . Conversely, another Ugandan study of 450 ART patients found that seeking care from traditional healers/spiritual healers was not significantly associated with lower CD4 counts at ART initiation 16 , suggesting that use of traditional healers did not delay ART initiation.…”
Section: Introductionmentioning
confidence: 99%